The Influence of Employees Communication, Rewards and Recognition and Employees Development on Employees Engagement in Newfield Exploration (Malaysia) - Azrina, Abdul Aziz (2012)
The main purpose of this study is to examine and to better understand on the drivers influencing employee engagement in Newfield Exploration (Malaysia). This study was done on 99 employees of Newfield Exploration (Malaysia) and data obtained from questionnaires and were being analyzed by using Statistical Package for Social Science (SPSS) version 16. The statistical method of Pearson Correlation was used to determine the existence of the relationship between the independent variables which are Employee Communication, Rewards and Recognition and Employee Development with the dependent variable : Employee Engagement. Regression Analysis was conducted to examine the most important independent variable among the employees in Newfield Exploration (Malaysia), and Cronbach Alpha was used to further illustrate the reliability test. Throughout the statistical analysis of correlation analysis, it is found that there is a significant relationship between the three independent variables, which are Employee Communication, Rewards and Recognition and Employee Development with the dependent variable : Employee Engagement. Among all three independent variable, employee communication is found to be the most independent variable in driving the employee engagement in Newfield Exploration (Malaysia). This study will assist and help Newfield Exploration (Malaysia) to improve on its current employee engagement initiatives, also further enhance and develop more employee engagement initiatives to improve the overall employee engagement level in Newfield